Neuroprotective Effect of Cardamom Oil Against Aluminum Induced Neurotoxicity in Rats - Auti, Sandip T.; Kulkarni, Yogesh A. (Frontiers in Neurology, 2019)
Acetylcholinesterase (AChE) is an enzyme involved in progression of Alzheimer’s disease (AD). Cardamom oil (CO) has been reported to have acetylcholinesterase inhibitory, antioxidant and anti-anxiety effects. Hence, we studied the effect of cardamom oil in aluminium chloride induced alzheimers disease in rats. AD was induced in Wistar rats with aluminium chloride (100 mg/kg, p.o.). Cardamom oil was administered concomitantly by oral route at dose of 100, 200 mg/kg for 42 days. Behavioural parameters like Morris water maze, elevated plus maze, passive avoidance test and locomotor activity were evaluated on day 21 and 42. AChE activity, oxidative stress parameters, histopathological studies and immunohistochemistry studies were carried out in hippocampus and cortex. Cardamom oil treatment showed significant improvement in behavioural parameters, inhibition of AChE activity (p<0.001) and reduction in oxidative stress in brain. Histopathological studies of hippocampus and cortex by haematoxylin, eosin and congo red stain showed inhibition of neuronal damage and amyloid β plaque formation with cardamom oil treatment. Immunohistochemistry showed, CO treatment inhibited amyloid β expression and upregulated brain derived neurotrophic factor (BDNF). The present study showed that, Cardamom oil has neuroprotective effect in Alzheimer's disease linked with inhibition of AChE activity and reduction in oxidative damage.